Analysis of neural crest cells from Charcot–Marie–Tooth disease patients demonstrates disease-relevant molecular signature. Issue 13 (6th September 2017) - Kitani-Morii, Fukiko; Imamura, Keiko; Kondo, Takayuki; Ohara, Ryo; Enami, Takako; Shibukawa, Ran; Yamamoto, Takuya; Sekiguchi, Kazuya; Toguchida, Junya; Mizuno, Toshiki; Nakagawa, Masanori; Inoue, Haruhisa
Abstract : Charcot–Marie–Tooth disease (CMT) is the most common inherited neuropathy. The majority of CMT is demyelinating type (demyelinating CMT) caused by Schwann cell involvement. Although a large number of genes responsible for demyelinating CMT have been found, the common molecular target of the pathophysiology caused by these different genes in demyelinating CMT is still unknown. We generated induced pluripotent stem cells (iPSCs) from healthy controls and patients with demyelinating CMT caused by duplication in peripheral myelin protein 22 kDa ( PMP22 ) or point mutations in myelin protein zero ( MPZ ) or early growth response 2 ( EGR2 ). iPSCs were differentiated into neural crest cells, progenitors of Schwann cells, followed by purification using the neural crest cell markers p75 and human natural killer-1. To identify a disease-relevant molecular signature at the early stage of demyelinating CMT, we conducted global gene expression analysis of iPSC-derived neural crest cells and found that a glutathione-mediated detoxification pathway was one of the related pathways in demyelinating CMT. mRNA expression of glutathione S -transferase theta 2 ( GSTT2 ), encoding an important enzyme for glutathione-mediated detoxification, and production of reactive oxygen species were increased in demyelinating CMT. Our study suggested that patient-iPSC-derived neural crest cells could be a cellular model for investigating genetically heterogeneous disease CMT and might provide a therapeutic target for the disease. Abstract : Supplemental Digital Content is available in the text.